SYARIAH STOCKS: A NORMATIVE ANALYSIS OF ISLAMIC LAW AND INVESTMENT PRACTICES IN INDONESIA - Umar, Zulkarnaini; Seruni, Puti Mayang; Falah, Muhammad; Krismen, Yudi (Universitas Syiah Kuala, 2024)
Syariah stocks have recently gained attention in the Islamic community, which relies on Shariah principles to guide investment decisions. Islam emphasizes the importance of profitable investments that benefit all parties involved, while prohibiting investments that involve uncertainty or exploitation. This article provides an overview of the position of stock shares in Islamic law. Using a normative legal research method, this study analyzed the relevant Islamic texts, including the Quran, Hadith, and Fatwas issued by scholars. Syariah stocks are specifically designed to meet the requirements of Islamic law, which emphasizes transparency, fairness, and ethics in financial transactions. The National Sharia Council of the Indonesian Ulama Assembly (DSN MUI) issued a Fatwa No. 80/DSN-MUI/III of 2011, outlining the implementation of Islamic principles in equity securities trading. The Fatwa stipulates that the means of payment must be known in terms of amount and form, whether in the form of money or goods, and that there should be no payment in the form of debt. Additionally, the time and place of delivery must be clearly specified based on the agreement between parties. This type of contract involves multiple parties, including banking institutions, and must be conducted in accordance with Islamic principles. The Fatwa has contributed to clarifying the terms of stock trading under Islamic law, providing a framework for Syariah stocks to operate within the boundaries of Islamic law.